Application of the Capture-Recapture Method in Estimating the Size of the Active Homosexual Male Population in Hangzhou City of China. (March 2015) - Zhou, Weihua; Huang, Manli; Wei, Ning; Hu, Shaohua; Wei, Erqing; Xu, Yi
The homosexual population is particularly susceptible to sexually transmitted disease because of various high-risk sexual behaviors among them. The authors explored the application of capture-recapture methods in estimating the size of the sexually active homosexual male population in Hangzhou. Homosexual men at 9 activity sites were investigated in Hangzhou, Zhejiang. The total active homosexual male population of Hangzhou estimated by the capture-recapture method and multiplier method was 2014 (95% confidence interval [CI] = 1899-2129) and 2012.5 (95% CI 1925 to 2101), respectively. This study shows that the capture-recapture method can be used to enumerate and provide accurate and reliable estimates of the active homosexual population in any area, provided that certain conditions are controlled.